Violence victimization and perpetration within the caregiver-patient relationship in schizophrenia: A cross-sectional study in Tunisia - Feten Fekih-Romdhane; Bochra Nourhène Saguem; Manel Stambouli; Souheil Hallit; Majda Cheour (PLoS ONE, 2025)
Background Family caregivers represent an integral part of the mental health care system in Tunisia, as well as in most of the low-to-middle-income countries and collectivist cultural backgrounds (i.e., communities that prioritizes the group over the individual). However, their task is burdensome, often associated with both experienced and perpetrated violence toward the patient. We aimed to shed light on the caregiver-patient relationship by investigating the prevalence and correlates of both violence victimization and violence perpetration in a Tunisian sample of caregivers of patients with schizophrenia. Method A paper-and-pencil self-administered questionnaire was used to collect data from participants. Caregivers (N = 110, aged 39.7 ± 12.5 years, 63.6% females) were asked questions about their experience of violence perpetration and victimization involving their relative with schizophrenia in the past 12 months. The Depression Anxiety and Stress Scales (DASS-21) and the abridged version of the Zarit Burden Interview (ZBI) were administered to all participants. Results Verbal violence was the most reported type of violence victimization (35.5%), followed by threat (25.5%), and physical violence (25.5%). In addition, 54.5% of caregivers disclosed having perpetrated verbal violence at least once against their ill relative. The most endorsed causes of violence victimization were symptoms of illness (57.3%) and refusal to adhere to treatment (49.1%). Multivariable analysis (logistic regression) revealed that caregivers’ levels of burden remained significantly associated with violence victimization occurrence (OR = 1.48; 95% CI 1.05; 2.09; p = .026), while having another person in charge of caring represented a significant factor associated with perpetration of any form of violence against patients (OR = .17; 95% CI.05;.62; p = .007). Conclusion Although preliminary and based on cross-sectional data and a relatively small sample size, our findings draw attention to the high prevalence of both violence perpetration and victimization within the caregiver-patient relationship in schizophrenia. Findings also identified caregivers’ burden and having another person in charge of caring as factors significantly associated with occurrence of any violence victimization and violence perpetration, respectively. These factors are potentially malleable, and may be helpful in targeting an at-risk population and developing appropriate prevention strategies.